2021
DOI: 10.1177/10600280211043278
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Multicomponent Protocol to Promote Sleep and Reduce Delirium in a Medical Intensive Care Unit

Abstract: Background: Evidence suggests that poor sleep increases risk of delirium. Because delirium is associated with poor outcomes, institutions have developed protocols to improve sleep in critically ill patients. Objective: To assess the impact of implementing a multicomponent sleep protocol. Methods: In this prospective, preimplementation and postimplementation evaluation, adult patients admitted to the medical intensive care unit (ICU) over 42 days were included. Outcomes evaluated included median delirium-free d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This difference, however, was not statistically significant. Contrary to this, a study by Darby et al [38 ▪▪ ] incorporating a similar sleep bundle into the existing ABCDEF bundle for delirium prevention did not show any improvement in sleep quality or rates of delirium. Definitive conclusions are challenged however by missing data within studies, particularly as it relates to compliance with assessments of delirium and sleep quality.…”
Section: Interventions To Improve Sleep and Circadian Rhythm In The Icumentioning
confidence: 59%
“…This difference, however, was not statistically significant. Contrary to this, a study by Darby et al [38 ▪▪ ] incorporating a similar sleep bundle into the existing ABCDEF bundle for delirium prevention did not show any improvement in sleep quality or rates of delirium. Definitive conclusions are challenged however by missing data within studies, particularly as it relates to compliance with assessments of delirium and sleep quality.…”
Section: Interventions To Improve Sleep and Circadian Rhythm In The Icumentioning
confidence: 59%
“…Cut-off scores for healthy sleep (population norms) have not yet been established, but there is beginning evidence that a score of 63 mm is a reliable cut-off score for good-quality sleep. 16 Darby et al 9 reported a prospective quality improvement study in which data were collected for delirium-free days After the implementation of a not dissimilar study by Patel et al 10 patients reported an increase in sleep quality (pre: 60.8 ± 3.5 vs. post: 75.9 ± 2.24 mm) and the incidence of delirium was lower (pre: 33 % [n = 55/167] vs. post: 14 % [n = 24/171]). In this study the difference between nocturnal mean light and sound levels and compliance measured before and after the implementation of the intervention indicated that clinicians adopted many components (sound pre: 68.8 ± 4.2 dB vs. post: 61.8 ± 9.1 dB; light levels per: 594 ± 88.2 lux vs. post: 301 ± 53.5 lux).…”
Section: Review Of the Evidencementioning
confidence: 99%
“…Darby et al 9 reported a prospective quality improvement study in which data were collected for delirium‐free days (1 [IQR 0–2.5] vs. 1 [0–2]) and RCSQ (59.4 [IQR 43.2–71.6] vs. 61.2 [49.9–75.5] mm) before and after the implementation of a multicomponent staged sleep protocol revealed no change in delirium and sleep outcomes. In this study, confounding factors were not controlled for in the analysis; the intervention was incremental (only patients who continued to experience poor sleep received interventions included in the additional stages, such as eye masks and melatonin) and stage 3 interventions included the administration of antipsychotics.…”
Section: Review Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…5 Although not recommended by PADIS, and despite questions regarding their benefit, medications with the potential to initiate or maintain sleep, or improve circadian entrainment, are often added to ICU sleep protocols. 57…”
Section: Introductionmentioning
confidence: 99%